2021
DOI: 10.1186/s40360-021-00494-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of alamandine on doxorubicin‑induced nephrotoxicity in rats

Abstract: Background This study aimed to evaluate the protective effects of alamandine, a new member of the angiotensin family, against doxorubicin (DOX)-induced nephrotoxicity in rats. Methods Rats were intraperitoneally injected with DOX (3.750 mg/kg/week) to reach a total cumulative dose of 15 mg/kg by day 35. Alamandine (50 µg/kg/day) was administered to the rats via mini-osmotic pumps for 42 days. At the end of the experiment, rats were placed in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Exposure to DXB significantly increased cardiorenal expression of p53, an important apoptotic mediator. Earlier studies demonstrated that DXB toxicity induces up-regulation in p53 protein in the kidney, testes and cardiac tissues [ 37 , 38 , 39 , 40 ]. However, COST treatment down-regulated cardiorenal apoptosis by inhibiting increases in p53 intensity, thus showing protective effects against DXB-mediated toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to DXB significantly increased cardiorenal expression of p53, an important apoptotic mediator. Earlier studies demonstrated that DXB toxicity induces up-regulation in p53 protein in the kidney, testes and cardiac tissues [ 37 , 38 , 39 , 40 ]. However, COST treatment down-regulated cardiorenal apoptosis by inhibiting increases in p53 intensity, thus showing protective effects against DXB-mediated toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activator NF-κB regulates various inflammatory factors and plays a significant role in the pathophysiology of the DOX-induced inflammatory cascade in organ injuries [ 46 , 47 , 48 ]. NF-κB activation influenced by ROS overproduction is mainly responsible for the changes in the inflammatory cascades via the mediation of pro-inflammatory cytokines and mediators (TNF-α, IL-1β, IL-6, COX-2, and iNOS) [ 49 ]. NF-κB activation is inevitable during the prevailing dominance of pro-inflammatory mediators, and this positive feedback mechanism is predicted to augment pro-inflammatory signals which aggravate tissue injuries [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alamandine (50 μ g/kg/day, S.C. for 42 days) also alleviated the negative proinflammatory effects of doxorubicin (DOX) (e.g., increased TNF- α , IL-1 β , IL-6, TGF- β , and NF- κ B levels) [ 59 , 60 ]. Moreover, a study in rats indicated that alamandine can drastically control DOX-induced cardiotoxicity and nephrotoxicity by altering rats' antioxidant status, apoptosis, and inflammatory cytokines [ 59 ].…”
Section: Alamandinementioning
confidence: 99%
“…Alamandine (50 μ g/kg/day, S.C. for 42 days) also alleviated the negative proinflammatory effects of doxorubicin (DOX) (e.g., increased TNF- α , IL-1 β , IL-6, TGF- β , and NF- κ B levels) [ 59 , 60 ]. Moreover, a study in rats indicated that alamandine can drastically control DOX-induced cardiotoxicity and nephrotoxicity by altering rats' antioxidant status, apoptosis, and inflammatory cytokines [ 59 ]. Furthermore, Liu et al recently showed that alamandine (2 μ g/kg/day, S.C. for 21 days) can inhibit bleomycin-induced lung fibrosis by reducing oxidative stress and activating autophagy through the MrgD receptor [ 61 ].…”
Section: Alamandinementioning
confidence: 99%